Systematic Review and Meta-Analysis of Published Studies on Endovascular Repair of Abdominal Aortic Aneurysm With the p-Branch - Wu, Haoliang; Zhang, Liwei; Li, Mingxing; Wei, Shunbo; Zhang, Cong; Bai, Hualong (Frontiers in Surgery, 2022)
Background: Endovascular treatment of juxtarenal or pararenal abdominal aortic aneurysms is more popular than open surgery, mainly because it reduces perioperative mortality and morbidity. The custom made fenestrated devices need to be tailored to each patient, so these devices require extra manufacturing and shipping time. The increased wait time may increase the risk of aneurysms rupture in some patients. In some situations, “Off-the-shelf” (OTS) fenestrated grafts can be used. The Cook Zenith p-Branch device (William Cook Australia, Brisbane, Australia) is a relatively common OTS. This study was to systematically evaluate all published experience with p-Branch. Methods: We searched the PubMed, Embase, and Cochrane to find literatures that reported on the outcomes of patients treated with the p-Branch stent grafts. Then we conducted assessment of quality and meta-analysis of the results. The primary end points were application rate of p-Branch stent graft (type A, B), technical success rate, and early re-intervention rate. We estimated pooled proportions and 95% confidence intervals (CIs). Results: Initial search of the literature included 111 articles, of which 7 studies were included in the end. A total of 260 patients were enrolled in these studies, and 218 patients were eventually treated with p-Branch. The pooled application rate of type A device was 48% (95% CI, 29% - 67%), and pooled application rate of type B device was 30% (95% CI, 16% - 44%). The pooled technical success rate was 87% (95% CI, 75% - 98%). The early re-intervention rate was 10% (95% CI, 3% - 17%). Midterm renal infarct rate (after 30 days) was 3% (95% CI, 0% - 6%). Midterm re-intervention rate (after 30 days) was 30% (95% CI, 3% - 57%). Midterm renal failure rate (after 30 days) was 6% (95% CI, 2% - 10%). Conclusions: This pooled analysis indicated an acceptable technical success rate after p-Branch stent graft implantation, with early and midterm re-intervention rate and renal failure rate that can not be ignored. The p-Branch repair of juxtarenal abdominal aortic aneurysms may be an appropriate and safe option, especially in emergency situations.